Integrated work-cell simulator and graphical control interface for a tele-operated underwater robotic vehicle - Tan, Kok Cheng. (2008)
A multimode URV topside control system is being developed to improve pilot's efficiency as well as to provide for off-line training support and mission rehearsal.